Autoethnography in the perspective of biographical research – some reflections on the method, material and ways of narrative analysis - Karkowska, Magda; Agnieszka Gralak (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
Presented text is a contribution to discussing autoethnography, methods, reflection, or the broader set of research and narrative practices that are involved in different visions of constructing knowledge and working with texts as a products of culture. As it says autoetnography without a trial to decide whether it is rather a kind of creative work, a literary genre close to autobiography, or rather a research technique for collecting biographical material in the process of creating a life story or documenting social events – has an interesting proposition in social science as well as literary science. The narrative emerging in the process of introspection is the basis for analyzing thesphere of human activity, based on open and hidden motives, solving problems by evaluating and confronting the emotions experienced in the process of reaching the internal conditions of our activities. Narrative, leading to biographical or self-biographical stories, also triggers reflection on life, summarizes past events, places itself in a broadly and narrowly understood social context, and thus has a developmental significance because of supporting self awareness and leading a human towards his higher destinations and better settling in the co-created world of life.